Analysis of the Application of Reliability, Availability, and Maintainability (RAM) Method in CNC Plasma Cutting Machine Maintenance at PT XYZ - Steven Trihero Baan Tandipayuk; Dira Ernawati , (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
This study aims to analyze the application of the Reliability, Availability, and Maintainability (RAM) method in the CNC Plasma Cutting machine maintenance system at PT XYZ as one of the main equipment in the production process in the maritime industry, especially in shipyard companies. The analysis was conducted based on machine operational data during a one-year observation period which includes operating time, planned downtime, unplanned downtime, and the number of machine failure events. A quantitative approach was used to calculate the Mean Time Between Failure (MTBF), Mean Time To Repair (MTTR), and Availability parameters as indicators of machine maintenance performance. The analysis results show that the CNC Plasma Cutting machine has an MTBF value of 103.2 hours, an MTTR of 2.54 hours, and an availability of 98.71%. These values indicate that the machine has a high level of reliability and availability, and a maintenance system that is able to restore the machine's condition in a relatively short time after a disruption occurs. However, unplanned downtime is still found which has the potential to affect the effectiveness of machine operations. Overall, the application of the RAM method is able to provide a comprehensive picture of machine maintenance performance and can be used as a basis for evaluation in preparing more targeted and data-based maintenance policies to support the continuity of the production process in shipbuilding companies.